Hypoxia Aggravates Neuron Ferroptosis in Early Brain Injury Following Subarachnoid Hemorrhage via NCOA4-Meditated Ferritinophagy - Zixuan Yuan; Xiaoming Zhou; Yan Zou; Bingtao Zhang; Yao Jian; Qi Wu; Shujuan Chen; Xin Zhang (MDPI AG, 2023)
The occurrence of early brain injury (EBI) significantly contributes to the unfavorable prognosis observed in patients with subarachnoid hemorrhage (SAH). During the process of EBI, a substantial quantity of iron permeates into the subarachnoid space and brain tissue, thereby raising concerns regarding its metabolism. To investigate the role and metabolic processes of excessive iron in neurons, we established both in vivo and in vitro models of SAH. We substantiated that ferritinophagy participates in iron metabolism disorders and promotes neuronal ferroptosis using an in vivo model, as detected by key proteins such as ferritin heavy chain 1, glutathione peroxidase 4, autophagy related 5, nuclear receptor coactivator 4 (NCOA4), LC3B, and electron microscopy results. By interfering with NCOA4 expression in vitro and in vivo, we confirmed the pivotal role of elevated NCOA4 levels in ferritinophagy during EBI. Additionally, our in vitro experiments demonstrated that the addition of oxyhemoglobin alone did not result in a significant upregulation of NCOA4 expression. However, simultaneous addition of oxyhemoglobin and hypoxia exposure provoked a marked increase in NCOA4 expression and heightened ferritinophagy in HT22 cells. Using YC-1 to inhibit hypoxia signaling in in vitro and in vitro models effectively attenuated neuronal ferroptosis. Collectively, we found that the hypoxic microenvironment during the process of EBI exaggerates iron metabolism abnormalities, leading to poor prognoses in SAH. The findings also offer a novel and potentially effective foundation for the treatment of SAH, with the aim of alleviating hypoxia.